British vision : observatie en verbeelding in de Britse kunst 1750-1950 - Hoozee, Robert; Gage, John; Hyman, Timothy (Brussel : Mercatorfonds, 2007)
Auerbach, Frank ; Bacon, Francis ; Blake, William ; Bomberg, David ; Brandt, Bill ; De Chirico, Giorgio ; Dickson Innes, James ; Epstein, Jacob ; Godwin, Fay ; Hepworth, Barbara ; Hitchens, Ivon ; Hunt, Holman ; John, Augustus ; Jones, David ; Kossof, Leon ; Lees, Derwent ; Martin, John ; Matisse, Henri ; Moore, Henry ; Nash, Paul ; Nicholson, Ben ; Nicholson, William ; Pasmore, Victor ; Quinton Pringle, John ; Roberts, William ; Spencer, Stanley ; Sutherland, Graham ; Turner, J.M.W. ; Wyndham Lewis, Percy
boek
Keywords: Verenigd Koninkrijk; Groot-Brittanië